Prevalence and characterization of verotoxigenic-Escherichia coli isolates from pigs in Malaysia - Wing, Sze Ho; Tan, Lai Kuan; Ooi, Peck Toung; Chew, Chieng Yeo; Kwai , Lin Thong (BioMed Central, 2013)
Postweaning diarrhea caused by pathogenic Escherichia coli, in particular verotoxigenic E. coli (VTEC), has caused significant economic losses in the pig farming industry worldwide. However, there is limited information on VTEC in Malaysia. The objective of this study was to characterize pathogenic E. coli isolated from post-weaning piglets and growers with respect to their antibiograms, carriage of extended-spectrum beta-lactamases, pathotypes, production of hemolysins and fimbrial adhesins, serotypes, and genotypes.